Cloud-based Optimized Intelligent Substation Secondary System Rapid Test Model and System Design - Rongrong JI; Mengzhi WANG; Guowei ZHOU; Qingyao LIU; Hai LI; Ruofan HUANG (Zhongguo dianli)
A fast testing scheme for secondary system equipment based on cloud-side optimization is proposed. The cloud-side optimization capability is utilized to propose a fast testing architecture secondary system equipment and to achieve the reduction of the dimension from the sub-module to the test package. The operations of switching the applied quantity, throwing and closing the soft and hard plates and starting and stopping the terminal are further considered, and a fast testing mathematical model aiming at the shortest time is proposed. The test sequence is optimized based on the improved whale optimization algorithm (SWOA). The effectiveness and accuracy of the proposed scheme are verified through simulation result.